PENDEKATAN ICARE (INTRODUCTION, CONNECTION, APPLICATION, REFLECTION, EXTENSION) DALAM LKPD PELAJARAN MATEMATIKA KELAS VII SMP - Luvi Antari; Syaifudin; Nia Pusvitasari (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2022)
This study aims to produce worksheets based on the ICARE approach that are valid and practical and have a potential effect on algebraic arithmetic operations material. This research is a development research or Development Research. The LKPD development process goes through two stages, namely the preliminary stage and the formative evaluation stage. The LKPD was declared valid after being validated by three experts based on: 1. ICARE characteristics, 2. The suitability of the material to basic competencies and indicators of competency achievement, and 3. Grammatical compatibility according to the General Guidelines for Indonesian Spelling (PUEBI). While the practicality of LKPD is seen from the responses of students in small groups in answering questions. The potential effect is seen from the results of students' final ability tests. student learning outcomes obtained an average final grade of 85.35 which means that student learning outcomes are classified as very good. So it can be concluded that the ICARE approach-based worksheets that have been developed have a potential effect on student learning outcomes.